Hubungan Self-efficacy dan Hasil Belajar Matematika: Studi Korelasional pada Siswa Kelas VIII SMP di Karawang - Firstianti, Lita; Marlina, Rina; Hidayati, Nita (Media Pendidikan Matematika, 2026)
The mathematics achievement of junior high school students in Indonesia remains relatively low, and self-efficacy as one of the psychological factors influencing academic achievement has received significant attention in educational research. However, studies linking self-efficacy to learning outcomes using daily test scores as an indicator of achievement remain limited. This study aims to examine the relationship between self-efficacy and mathematics learning outcomes among 40 eighth-grade students who have completed the mathematics curriculum and taken daily quizzes at a junior high school in Karawang. The approach used in this study is quantitative with a correlational design. Self-efficacy was measured using a validated questionnaire adapted from Bandura’s scale, while learning outcome data were obtained from daily mathematics test scores. After the normality and linearity tests were met, the data were analyzed using Pearson’s Product-Moment correlation. The results indicate a positive and significant relationship between self-efficacy and mathematics learning outcomes ( ) in the high category. However, 95% of the students had not yet met the minimum passing score, suggesting that self-efficacy alone is insufficient without strong foundational skills and high-quality instruction. These findings underscore the need for instructional strategies that simultaneously strengthen students’ self-confidence and mathematical competence.